The mortality benefit of carvedilol versus bisoprolol in patients with heart failure with reduced ejection fraction - Ki Hong Choi; Ga Yeon Lee; Jin-Oh Choi; Eun-Seok Jeon; Hae-Young Lee; Sang Eun Lee; Jae-Joong Kim; Shung Chull Chae; Sang Hong Baek; Seok-Min Kang; Dong-Ju Choi; Byung-Su Yoo; et al. (The Korean Journal of Internal Medicine, 2019)
Background/Aims It is unknown whether different β-blockers (BBs) have variable effects on long-term survival of patients with heart failure with reduced ejection fraction (HFrEF). This study compares the effects of two BBs, carvedilol and bisoprolol, on survival in patients with HFrEF. Methods The Korean Acute Heart Failure (KorAHF) registry is a prospective multicenter cohort that includes 5,625 patients who were hospitalized for acute heart failure (AHF). We selected 3,016 patients with HFrEF and divided this study population into two groups: BB at discharge (n = 1,707) or no BB at discharge (n = 1,309). Among patients with BB at discharge, subgroups were formed based on carvedilol prescription (n = 831), or bisoprolol prescription (n = 553). Propensity score matching analysis was performed. Results Among patients who were prescribed a BB at discharge, 60.5% received carvedilol and 32.7% received bisoprolol. There was a significant reduction in allcause mortality in those patients with HFrEF prescribed a BB at discharge compared to those who were not (BB vs. no BB, 26.1% vs. 40.8%; hazard ratio [HR], 0.59; 95% confidence interval [CI], 0.52 to 0.67; p < 0.001). However, there was no significant difference in the rate of all-cause mortality between those receiving different types of BB (carvedilol vs. bisoprolol, 27.5% vs. 23.5%; HR, 1.21; 95% CI, 0.99 to 1.47; p = 0.07). Similar results were observed after propensity score matching analysis (508 pairs, 26.2% vs. 23.8%; HR, 1.10; 95% CI, 0.86 to 1.40; p = 0.47). Conclusions In the treatment of AHF with reduced EF after hospitalization, mortality benefits of carvedilol and bisoprolol were comparable.